Integrity and Relatedness: Some Critical Reflections on Congregationalism and Connexionalism*. (2nd January 2017) - Colwell, John
ABSTRACT: The following paper discusses the manner in which the liberty of the local church should be qualified if a local gathering is to be recognized both as validly a church and validly a baptist church. With these qualifications in mind the paper then revisits the Baptist Union of Great Britain's Declaration of Principle, noting the commitment to a congregational church order together with a commitment to credo-baptism as the key identifying markers. Finally the paper explores (and perhaps exposes) the ways in which a commitment to congregational order is being undermined, both by local churches and by connexional gatherings, and how this undermining itself undermines our Baptist identity. Tensions between congregationalism and connexionalism might be lessened with a mutual recognition of the integrity of a congregational dynamic.